The sources of the Russian-Portuguese relations - Stanislav I. Cherniavskiy (Ибероамериканские тетради)
The article is devoted to the most important stages in the history of Russian-Portuguese relations (1722-1799) - from the ﬁrst study of diplomatic contacts (1722) to conclusion of a bilateral Defense Treaty of the Union (1799). On the basis of archival materials, the author analyzes the complex diplomatic activity on both sides, which led to the establishment of friendly, trusting relationship Lisbon and St. Petersburg